1994
DOI: 10.1093/rheumatology/33.8.754
|View full text |Cite
|
Sign up to set email alerts
|

The Psychosocial and Clinical Status of Younger Women With Early Rheumatoid Arthritis: A Longitudinal Study With Frequent Measures

Abstract: A longitudinal study of 75 young women (median age 43 yr) with early RA was performed with psychological, clinical and functional status measured every 4 months for up to 44 months. The aim was to describe functional changes, and to estimate the association between psychosocial variables and function in the early years after diagnosis. Function was measured by the Stanford Health Assessment Questionnaire (HAQ) and improved on average by about 10% per year with most improvement occurring over the first year. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 0 publications
4
14
0
Order By: Relevance
“…As such, the stability of trajectories after 3 years as described here is a novel finding. Considering the sample as a whole there was evidence for a slight reduction in distress in the first year after diagnosis, consistent with several previous reports [8][9][10][11][12]. Although we used a different methodology, our findings are comparable to those of Persson et al [9] who also observed around 12% of the sample as experiencing chronically high levels.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As such, the stability of trajectories after 3 years as described here is a novel finding. Considering the sample as a whole there was evidence for a slight reduction in distress in the first year after diagnosis, consistent with several previous reports [8][9][10][11][12]. Although we used a different methodology, our findings are comparable to those of Persson et al [9] who also observed around 12% of the sample as experiencing chronically high levels.…”
Section: Discussionsupporting
confidence: 91%
“…Although findings are broadly ambiguous, there is some indication of a small improvement in symptoms of psychological distress particularly during the early course of the disease. Five studies have reported significant improvement in psychological distress [8][9][10][11][12], whereas only one study has shown a significant worsening [13]. However, a further seven studies find that levels are stable (or rather, do not change significantly) over time [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In a large study (N = 1578) by Pilowsky [22], a depressed group of RA sufferers was found to perceive their illness as being more serious and feel hopeless about a cure compared with non-depressed RA group, even when the actual severity of arthritis was adjusted for. One of the first longitudinal studies to document the importance of illness perception in RA was a study involving a sample of 75 younger female patients [23]. They found that depression was consistently predicted by physical disability, pain, passive coping and beliefs about the consequences of RA.…”
Section: Discussionmentioning
confidence: 99%
“…anxiety, depression) has been shown to considerably in fluence such outcome measures [6][7][8][9], Some controversy on this issue is still continuing. While one recent study [4] could not establish a significant relationship between psy chological variables and functional status in RA patients at two time points , another study [10] clearly highlighted their importance. The fact that scoring of self-ratings of functioning may be obscured by psychosocial factors should raise concern regarding the necessity to assess somatic, psychosocial, as well as correlates self-rated by patients, in parallel as emphasized earlier [6][7][8].…”
Section: Introductionmentioning
confidence: 92%